The impact of the circular economy on the value chain: In the context of the Portuguese footwear industry - Balula, Diogo Coutinho (2023)
This work deals with a study on the practicality of applying business models based on a circular economy in the Portuguese footwear industry. The aim is to identify the fundamental issues underlying the standardised circular model, as well as to relate the driving factors and obstacles in terms of recognising the potential facilitators of the system as a whole, so that these new alternative business models can be applied successfully. In order to carry out this research, questions were asked of consumers of this type of product and interviews were conducted with companies in the sector, which were then standardised and analysed in order to establish relationships between both surveys. The scope of this work was to study the Portuguese point of view of the footwear industry and the potential of this market in terms of its circularisation, bearing in mind its limitations, which come from a rather relative analysis, given the fact that it relies heavily on qualitative data. After obtaining the data, we can understand that this issue should be analysed from a more holistic point of view, as the adoption of these models directly affects two opposite points in the chain, customers and companies, due to the high costs associated with a change in business model, which would always affect both sides, even though change is recognised as essential for the future. Overall, we are just a small step away from this change. We just need more innovative ideas to overcome this very important cost barrier.